A Case Report On Abnormal Uterine Bleeding with Multi-System Disorders: LifeScience-Gynaecology - S, Dr. Niranjani; Revathy, Dr. T.G.; Varrshine.R, Dr. (International Journal of Life Science and Pharma Research, 2023)
Autoimmune disease is a condition that attacks the immune system and leads to multi-system disorders like systemiclupus erythematosus and rheumatoid disorders, which initiates self-directed immune responses that result in clinical diseases,mainly in obstetrics conditions like recurrent pregnancy loss, pre-eclampsia are common. The study aimed to identify therelationship between connective tissue disorders and abnormal uterine bleeding patterns. A rare case of abnormal uterinebleeding with a past history of recurrent pregnancy loss was presented in the casualty with excessive menstrual bleeding in astate of hypovolemic shock. The patient complained of generalised malaise, giddiness, breathlessness, and palpitations for thepast 2 months. She suffered recurrent epistaxis for the past 2 months and experienced symptoms like loss of appetite, recurrentvomiting for the past 15 – 20 days, and rashes over the face and cheeks for 6 months. Her haemoglobin was 2.4g/dL, and theplatelets were less than 10,000 with bicytopenia at the time of admission She was shifted to ICU and haemodynamicallystabilized by packed red blood cells, fresh frozen plasma, and platelets. Following this, she was treated with antifibrinolytics, andsevere anaemia was corrected with multiple PRBC transfusions. Multiple single-donor platelet transfusions were also done. Afterrecovery, the patient was discharged with an advice to continue hydroxychloroquine. Immune dysregulation and inflammationtogether contribute to the development of menstrual disorders among women with Rheumatoid Disorders which can be wellmanaged with systematic therapeutic plans at the initial stage.